Impact of supply voltage distortion on the current harmonic emission of non-linear loads (2015)
Electronic devices have a non-linear characteristic and emit harmonics into the low voltage grid. Different harmonic studies analyze their impact on the grids based on different types of harmonic models. The most used model is the constant current source. Measurements have shown that the harmonic currents emitted by electronic devices depend on the circuit topology and the existing supply voltage distortion. This paper quantifies the impact of supply voltage distortion on the harmonic current emission of individual devices and the summation of multiple devices. After a classification of the commonly used circuit topologies a time-domain model is developed for each of them. Then the individual and combined impact of voltage harmonics on the harmonic current emission of the modeled devices is analyzed based on simulations. Finally the impact of voltage distortion on the summation of multiple devices is analyzed and the accuracy of constant current source models is evaluated.